Barriers and enablers to climate change adaptation in hierarchical governance systems: the case of Vietnam. Issue 4 (4th July 2018) - Phuong, Le Thi Hong; Biesbroek, G. Robbert; Wals, Arjen E. J.
ABSTRACT: Governments fulfil important roles in increasing the adaptive capacity of local communities to respond to climate change impacts, particularly in developing countries. Existing studies on how governments enable and constrain the ways in which local level communities learn and build their adaptive capacity, however, generally adopt network or market-oriented types of governance. However, the most vulnerable regions to climate change impact in the world are generally governed through hierarchical policy systems. This research aims to understand how the hierarchical policy system in Vietnam creates enables and/or constrains the policy capacity of policy actors to contribute to effective climate change adaptation. We conducted interviews ( n  = 26) with key actors at multiple levels of government. Our findings show the importance of clear legal institutions, available financing for implementing policies, and the training of governmental staff, particularly at district and commune levels where the policy capacities are generally too low to deal with climate change impacts. We conclude that any efforts to support local actors (i.e. smallholder farmers) should include investments in policy capacity to ensure uptake and upscaling of adaptation actions more broadly.